Beyond stewardship: common world pedagogies for the Anthropocene. Issue 10 (26th November 2017) - Taylor, Affrica
Abstract: Interdisciplinary Anthropocene debates are prompting calls for a paradigm shift in thinking about what it means to be human and about our place and agency in the world. Within environmental education, sustainability remains centre stage and oddly disconnected from these Anthropocene debates. Framed by humanist principles, most sustainability education promotes humans as the primary change agents and environmental stewards. Although well-meaning, stewardship pedagogies do not provide the paradigm shift that is needed to respond to the implications of the Anthropocene. Anthropocene-attuned 'common worlds' pedagogies move beyond the limits of humanist stewardship framings. Based upon a more-than-human relational ontology, common world pedagogies reposition childhood and learning within inextricably entangled life-worlds, and seek to learn from what is already going on in these worlds. This article illustrates how a common worlds approach to learning 'with' nonhuman others rather than 'about' them and 'on their behalf' offers an alternative to stewardship pedagogies.